Reinterpretasi Teologis terhadap Roh dalam 1 Samuel 28:3-20: antara Roh Samuel, Roh Allah dan Iblis - Yan Mangoli, Yefta; Damanik, Hilderia (JOURNAL of THEOLOGICAL STUDENTS, 2025)
The story of Saul’s consultation with a medium in 1 Samuel 28:3–20 is one of the most controversial passages in the Old Testament, particularly concerning the identity of the spirit that appeared at Endor. This practice is known in Greek as necromancy. According to the Torah, such practices are condemned as an abomination before God (Deut. 18:10–18) and bring His wrath upon those who perform them. This study aims to provide a theological analysis of the identity of the spirit in this passage and to examine various theological perspectives surrounding it. The research employs a qualitative method with a biblical exegesis and theological analysis approach, including a close reading of the biblical text, theological literature review, and comparative interpretation from different Christian theological traditions. Based on the biblical context and theological principles, this study concludes that the spirit at Endor is most consistently understood as a deceptive demonic manifestation imitating Samuel, aligning with the Bible’s firm prohibition against necromancy.